Experimental and Theoretical Analyses of Azulene Synthesis from Tropones and Active Methylene Compounds: Reaction of 2-Methoxytropone and Malononitrile - Machiguchi, Takahisa; Hasegawa, Toshio; Yamabe, Shinichi; Minato, Tsutomu; Yamazaki, Shoko; Nozoe, Tetsuo (Journal of organic chemistry, 2012)
A representative azulene formation from an active troponoid precursor (2-methoxytropone) and an active methylene compound (malononitrile) has been analyzed both experimentally and theoretically. 2H-Tracer experiments using 2-methoxy[3,5,7-2H3]tropone (2-d 3) and malononitrile anion give 2-amino-1,3-dicyano[4,6,8-2H3]azulene (1-d 3) in quantitative yield. New and stable 2H-incorporated reaction intermediates have been isolated, and main intermediates have been detected by careful low-temperature NMR measurements. The detection has been guided by mechanistic considerations and B3LYP/6-31(+)G(d) calculations. The facile and quantitative one-pot formation of azulene 1 has been found to consist of a number of consecutive elementary processes: (a) The troponoid substrate, 2-methoxytropone (2), is subject to a nucleophilic substitution by the attack of malononitrile anion (HC(CN)2 –) to form a Meisenheimer-type complex 3, which is rapidly converted to 2-troponylmalononitrile anion (5). (b) The anion 5 is converted to an isolable intermediate, 2-imino-2H-cyclohepta[b]furan-3-carbonitrile (6), by the first ring closure in the reaction. (c) A nucleophilic addition of the second HC(CN)2 – toward the imine 6 at the C-8a position produces the second Meisenheimer-type adduct 7. (d) The second ring closure leads to 1-carbamoyl-1,3-dicyano-2-imino-2,3-dihydroazulene (11). A base attacks the imine 11, which results in generation of a conjugate base 12 of the final product, azulene 1.